PERIODONTAL DISEASE AND COMPLICATIONS IN THE CONTEXT OF THE COVID-19 PANDEMIC. INACTIVATION OF PATHOGENS AT THE LEVEL OF A DENTAL OFFICE IN THE CONTEXT OF THE PANDEMIC. REVIEW. - Ionuț-Daniel G; Liliana Pasarin; Ana-Emanuela Botez; Doinita Temelie-Olinici; Ionut-Catalin Botezatu; Darius Sandu; Ruxandra Stan; Carmen Elena Cotrutz (Romanian Dental Association for Education, 2023)
When a disease is new to humans, only very few people are immune to it. In such cases, there is no vaccine and the result can be a rapid increase in the incidence of the disease. How dangerous or deadly that disease is - it all depends on the specific virus in question and the general state of health of each individual patient. If a disease does not only spread regionally but ends up affecting entire countries and continents, then experts speak of a pandemic. Periodontal disease is a bacterial infection that causes inflammation of the supporting tissues of the tooth. Experts say that there is a dangerous link between this and the COVID-19 infection, which leads to hospitalization or even admission to intensive care, periodontal disease can lead to complications of Covid-19. The association between coronavirus disease 2019 infection and periodontitis has also been investigated in the retrospective studies. In the current context we have solutions to eradicate already known pathogens, but new pathogens or changes to existing ones occur that require time and research to find a solution.